Dificuldades de professores nativos e não nativos de português como língua adicional em diferentes contextos - Café, Paula Tuany Silva (2020)
This Master's thesis addresses two fronts in linguistic studies: such as Teacher Education and Teaching Portuguese for Speakers of Other Languages. Teacher education was addressed here as fundamental in the construction of teaching knowledge, belonging to the theoretical axis of Applied Linguistics. Among the various terminologies that characterize the teaching of Portuguese for Speakers of Other Languages, it was adopted here Portuguese as an Additional Language (PAL/PLA). This study was born from a personal conflict: being a native speaker of Portuguese, how can I find so many difficulties in teaching my language to non-native speakers? Therefore, this research study aims to identify common and divergent aspects among the difficulties of native teachers and non-native teachers of PAL/PLA in different contexts. In order to achieve these objectives, it followed a qualitative approach and used questionnaire and interview as data collection instruments. The subjects participating in this research study were sixteen teachers from different contexts, native speakers and non-native speakers of Portuguese. All sixteen teachers answered the questionnaire and four of them were interviewed. To assist in the data analysis, the participating teachers were grouped into four quadrants, according to criteria related to their origin (whether they were native or non-native speakers of Portuguese) and to the context where they work (whether in a country where Portuguese is the first language or in a country where Portuguese is not the first language). To analyze the results, theories of teacher education, aspects of language teacher education, difficulties and challenges in the language teacher profession, as well as the concepts of native and non-native teacher of PAL/PLA were discussed. The results indicated difficulties related to language, to language teaching, to language teaching planning, and to the teacher profession and their professional journey. Moreover, the results showed that these difficulties sometimes converge or diverge not only according to the fact of being native or non-native speakers of Portuguese and of the language context where they work but also according to other factors, such as the teachers’ professional experience and education, and their students’ language level and needs. Based on the results, a set of challenges for PAL/PLA teacher education are proposed.